A Bound on the Number of Edges in Graphs Without an Even Cycle. (7th April 2016) - BUKH, BORIS; JIANG, ZILIN
Abstract : We show that, for each fixed k, an n -vertex graph not containing a cycle of length 2 k has at most $80\sqrt{k\log k}· n^{1+1/k}+O(n)$ edges.